The Relevance of Object Size to the Recognizability of Drawings by Individuals with Congenital Blindness. (May 2019) - Szubielska, Magdalena; Niestorowicz, Ewa; Marek, Bogusław
Introduction: The aim of this study was to determine whether individuals with congenital blindness make more recognizable drawings of known objects that are furniture sized (table, man, tree) rather than hand sized (egg, coconut, banana; Hypothesis 1). We also investigated whether knowledge that the tactile drawings had been produced by people who are blind increased judges' perceptions of their recognizability (Hypothesis 2). Methods: The raised-line drawings were made by children and teenagers who are blind and had no prior experience in tactile graphics. After a minimal initial training in line drawing, the subjects were asked to draw six objects from memory. The judges used a 7-point Likert-type scale to assess recognizability. All objects were identified for the judges prior to their assessment. One group of judges was told that the drawings they were assessing were made by persons who are blind, while the second group was informed that the drawings were made without the use of sight. Results: The real-life size of the objects depicted in the drawings affected judges' perception of their recognizability. Depictions of hand-sized objects were found to be less recognizable than were depictions of furniture-sized objects. Knowledge of the artists' blindness had no effect on the judgments of recognizability. Discussion: Hypothesis 1 was confirmed, which suggests that individuals with congenital blindness have more difficulty in creating drawings of hand-sized objects than they did creating drawings of furniture-sized objects. Hypothesis 2 was not confirmed, which is inconsistent with the results of previous research in which the awareness of the artists' disability status influenced the assessment of the artworks. Although the present research focused on recognizability, the issue in earlier research was aesthetic judgment. Implications for practitioners: Although few people would question the importance of illustrations in books for sighted children, the value of tactile graphics and the benefits of engaging children who have visual impairments in making and exploring raised-line drawings are not always understood. Full participation in subjects that rely on visual information such as geometry, art, and geography by learners who are born blind requires access to tactile graphics. Basic training in raised-line drawing may be sufficient for some children, particularly those who are older (aged 10 years or more), with congenital blindness who have never drawn before to create from memory recognizable drawings of known objects, especially larger objects.